Show that if $f:[0,1]\to \mathbb{R}$ and$$\lim \limits _{n\to \infty}\frac{f(x_1)+\cdots + f(x_n)}{n}$$exists whenever$$\lim \limits _{n\to \infty}\frac{x_1+\cdots + x_n}{n}$$exists, where $(x_n)$ is a sequence of real numbers, then $f$ is continuous.

It suffices to show that if $x_n\to x$, then $f(x_n)\to f(x)$. It might be useful to show this via a contradiction; suppose there is a sequence $x_n$ so that $x_n\to x\in \mathbb{R}$ but $f(x_n)\not \to f(x)$. We know that $\dfrac{f(x_1)+\cdots +f(x_n)}n$ exists and equals $L$, say. By definition, there exists $\varepsilon >0$ so that for all $N$, $\exists n\geq N$ such that $|f(x_n)-f(x)|\geq \varepsilon$. But I'm not sure how to get a contradiction from here.

  • $\begingroup$ $(f(x_1)+\cdots + f(x_n))/n$ and $(x_1+\cdots + x_n)/n$ always exist (unless $n=0$.) Is there a $\lim$ missing somewhere? $\endgroup$ Aug 5 at 22:05
  • $\begingroup$ @JairTaylor yes. $\endgroup$
    – Gord452
    Aug 5 at 22:51

2 Answers 2


Let $x_n \to x$

$$L := \liminf\limits_{n\to\infty} f\left(x_n\right)$$

There is an increasing sequence of integers $\left(\ell_p\right)_p$ such that $$\lim_{p\to\infty} f\left(x_{\ell_p}\right) = L$$

I will assume that $-\infty <L < \infty$, Using the fact that:

$$\forall m\in \Bbb N;\; \lim_{n\to\infty} \frac{1}{n+m}\left(\sum_{k=1}^n f\left(x_{\ell_k}\right)+ mf(x)\right) = L$$ and $$\forall n\in \Bbb N;\; \lim_{m\to\infty} \frac{1}{n+m}\left(\sum_{k=1}^n f\left(x_{\ell_k}\right)+ mf(x)\right) = f(x)$$

you can easily construct (by induction) two increasing sequences of integers $\left(m_p\right)_{p\in \Bbb N}$, $\left(n_p\right)_{p\in \Bbb N}$, such that $m_0= n_0 = 0$ and

  • $\forall p\in\Bbb N_{\ge 1},$
    $$\left|\frac1{n_{p}+m_p}\left(\sum_{k=1}^{n_{p}} f\left(x_{\ell_k}\right) + m_pf(x)\right) - f(x)\right| < \frac1{p};$$ and $$\left|\frac1{n_{p+1}+m_p}\left(\sum_{k=1}^{n_{p+1}} f\left(x_{\ell_k}\right) + m_pf(x)\right) - L\right| < \frac1{p}$$

Let $$z_k = \begin{cases}x_{\ell_{k-m_p}} & \text{if $n_p+m_p < k \le n_{p+1}+m_p$}\\ x & \text{if $n_{p+1} + m_p < k \le n_{p+1} + m_{p+1}$}\end{cases}$$

So $$\limsup_{k\to \infty}\left|z_k-x\right|\le \limsup_{k\to \infty} \left|x_{\ell_k}-x\right| = 0$$

This proves that: $\lim\limits_{k\to\infty} z_k = x$, So $$\lim_{n\to\infty} \frac1n \sum_{k=1}^n f\left(z_k\right)$$ exists. On the other hand $$\frac1{n_p + m_p}\sum_{k=1}^{n_p+m_p}f(z_k) = \frac1{n_{p}+m_p}\left(\sum_{k=1}^{n_{p}} f\left(x_{\ell_k}\right) + m_pf(x)\right) \underset {p\to \infty} \to f(x)$$

and $$\frac1{n_{p+1} + m_p}\sum_{k=1}^{n_{p+1}+m_p}f(z_k) = \frac1{n_{p+1}+m_p}\left(\sum_{k=1}^{n_{p+1}} f\left(x_{\ell_k}\right) + m_pf(x)\right) \underset {p\to \infty} \to L$$

By unicity of the limit $L=f(x)$. By doing the same thing for the $\limsup$, you have $$f(x) = \liminf_{n\to\infty} f\left(x_n\right) = \limsup_{n\to \infty} f\left(x_n\right).$$


First show that if $x_n\rightarrow x$, then $\frac{\sum_{i=1}^n x_i}{n}\rightarrow x$ (and if $0\le x_n \le 1$, so is $0\le\frac{\sum_{i=1}^n x_i}{n}\le1$, we don't have to worry about the domain at all).

Now by the condition, $a:=\lim\frac{\sum_{i=1}^n f(x_i)}{n}$ exists. If $f(x)\not=a$, then the strategy is clear: Adding any number of $x$ to $x_n$ to create $\{y_i\}$ won't change the fact that the average $\frac{\sum_{i=1}^ny_i}{n}$ still converges, but it would make the average $\frac{\sum_{i=1}^n y_i}{n}$ oscillate around $a$ and $f(x)$.

To be more specific, first we pick $y_1=x_1, \cdots, y_n=x_n$ such that $\frac{\sum_{i=1}^n y_i}{n}$ is very close to $a$, now we set $y_{n+1}=\cdots = y_m = x$ for sufficiently large $m$ to bring the average close to $f(x)$, and then back to set $y_{m+1}=x_{n+1}, \cdots$ to bring the average once again close to $a$, and so on.

This shows $f(x) = \lim \frac{\sum_{i=1}^n f(x_i)}{n}$. Now if $f(x_n)$ doesn't converge to $f(x)$, we may use similar strategy to pick a subsequence such that the average oscillate.

  • $\begingroup$ I don't understand this argument. If you replace any number of $x_n$'s with $x,$ the average $\dfrac{\sum_{i=1}^n y_i}n$ will converge to $x$. Why does the average oscillate around a and f(x)? $\endgroup$
    – Gord452
    Aug 6 at 0:11
  • $\begingroup$ @Gord452, not to replace any of the $x_n$, but to add bunch of $x$ into the sequence in certain places, so the average occillates. $\endgroup$ Aug 6 at 0:23
  • $\begingroup$ yeah it needs a lot more rigor as the other answer demonstrates. $\endgroup$
    – dezdichado
    Aug 6 at 3:10

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.